2020
DOI: 10.1248/bpb.b20-00428
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Skin Toxicities Associated with Bendamustine-Based Chemotherapy in Patients with Non-Hodgkin Lymphoma

Abstract: Bendamustine plays an especially important role as a treatment for non-Hodgkin lymphoma (NHL). However, patients administered bendamustine alone or in combination with rituximab (BR) may experience drug-associated skin toxicities that can profoundly impact their health-related QOL through both physical discomfort and psychological distress. Moreover, worsening skin symptoms may lead to dose reduction or termination in the management of cancer chemotherapy. We retrospectively investigated patient backgrounds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Uchida et al analyzed 95 patients with non-Hodgkin's lymphoma who received bendamustine alone or BR therapy and reported that no prior treatment was a significant factor in skin toxicity. 16 In our study, 13/20 (65%) newly diagnosed patients developed rash and 14/45 (31%) relapsed/ refractory patients developed rash, demonstrating a signifi- Table 3. Characteristics of patients who developed rash after bendamustine and those who did not WHO, World Health Organization; MALT, mucosa-associated lymphoid tissue; WBC, white blood cell cant difference (p=0.0147).…”
supporting
confidence: 49%
“…Uchida et al analyzed 95 patients with non-Hodgkin's lymphoma who received bendamustine alone or BR therapy and reported that no prior treatment was a significant factor in skin toxicity. 16 In our study, 13/20 (65%) newly diagnosed patients developed rash and 14/45 (31%) relapsed/ refractory patients developed rash, demonstrating a signifi- Table 3. Characteristics of patients who developed rash after bendamustine and those who did not WHO, World Health Organization; MALT, mucosa-associated lymphoid tissue; WBC, white blood cell cant difference (p=0.0147).…”
supporting
confidence: 49%
“…Recently, Uchida and colleagues reported that non‐prior chemotherapy was a significantly high‐risk factor for skin toxicities in patients with NHL receiving bendamustine alone or with rituximab. 36 The underlying mechanism was not clarified; however, they speculated that T‐cell function was maintained in chemotherapy‐naïve patients compared with that in relapsed or refractory patients. Regarding skin AEs in tirabrutinib, further studies would be required.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rate of skin AEs was obviously higher in Cohort A in the present study. Recently, Uchida and colleagues reported that non‐prior chemotherapy was a significantly high‐risk factor for skin toxicities in patients with NHL receiving bendamustine alone or with rituximab 36 …”
Section: Discussionmentioning
confidence: 99%
“…However, adverse effects such as fever, memory loss, anxiety, and rash have been noted during or after discontinuation of treatment ( Yi et al, 2022 ). Furthermore, serious complications like progressive multifocal leukoencephalopathy (PML) have been reported, including a case in a patient with non-Hodgkin follicular lymphoma post hematopoietic stem cell transplantation and rituximab-bendamustine therapy, where JC Virus DNA was detected in both peripheral blood and cerebrospinal fluid ( Uchida Trociukas et al, 2020 ). A retrospective study of 95 patients also highlighted non-prior chemotherapy as a significant risk factor for skin toxicities among NHL patients treated with bendamustine alone or in combination with rituximab (BR therapy).…”
Section: Introductionmentioning
confidence: 99%